A comparison of the extraction procedures and quantification methods for the chromatographic determination of polycyclic aromatic hydrocarbons in charcoal grilled meat and fish - Viegas, O (2012)
A method for analysis of 15 PAHs in charcoal-grilled meat/fish was established by high performance liquid chromatography and fluorescence detection. Gradient elution was performed with methanol/water/ethyl acetate. maxima excitation and emission wavelengths were selected for each PAH. Retention times were very stable with coefficients of variation below 0.24% within analytical day and below 0.60% across analytical days. Two different methods of cleanup and pre-concentration steps were compared. Solvent extraction assisted by sonication carried out with n-hexane on 2 g of lyophilized meat or 1 g of lyophilized fish allowed to obtain high sensitivity, reproducibility and better extraction efficiency. Limits of quantification (LOQs, s/n = 10) were lower than 0.01 ng/g of meat wet weight and lower than 0.02 ng/g of fish wet weight for all PAHs (except for Na, Fl and IP that were lower than 0.1 ng/g). Two different quantification methods were compared. Standard addition method compensated PAHs losses due to incomplete extraction and it is recommended for analyses of grilled meat and fish samples that usually contain very low amounts of the eight high molecular weight PAHs (BaA, Ch, BbF, BkF, BaP, IP, BgP, DhA).